Spatial Transformation and Accessibility Efficiency of Transportation Network with Land Use in the Context of Chiang Mai Comprehensive Plan - Summaniti, Luxana; Summaniti, Siriwat (Journal of Architectural/Planning Research and Studies (JARS), 2017)
This spatial research aimed to analysis the accessibility efficiency of transport network plan and land use plan in the context of Chiang Mai comprehensive plan since 1984 which the first modification in 1989, the second modification in 1999 and the latest modification in 2012. The study was undertaken by documentary analysis, surveying, Geo Informatics System analysis, an analysis of land use plan and transportation network plan of Chiang Mai comprehensive plan including theory and Space Syntax technique. They were all used to analyze the morphological spatial structure of transportation network plan. It was found that the area of Chiang Mai comprehensive plan was increased from 106.0 square kilometers in 1984 to 429.0 square kilometers in 1984 and at the present time. On average, the accessibility efficiency indexes of changes of the morphological structure of the transportation network plan measured by the Space Syntax Model were 0.279821, 0.205415, 0.203256 and 0.214098, respectively. The characteristics of the transportation network were in the forms of a ring-road and a radial ring-road linking from the city center. Both were in conjunction with the schemes of land use types in Chiang Mai City Center for commercial purposes and very dense residential areas surrounded by medium and less density residential areas interspersing with rural and agricultural areas. The characteristic of morphological structure of the city center in 1984 was in the center of Chiang Mai city. Later, in the year 1989, it was extended to the South. From the year 1999 up until the present time, it had been extended to the East along the National Highway No. 1. Moreover, the accessibility efficiency index at the junction of the ring-road and the radial ring-road was higher than those of other areas. This brought about the blooming of suburb centers since 1999 which had a tendency to cause changes to land use of the mentioned suburban, rural and agricultural areas. Finally, a main factor of the spatial changes was the result of accessibility efficiency to the aforementioned transportation network. Therefore, in the future, measures to control the land utilization in Chiang Mai to reduce the negative impacts on suburban rural and agricultural areas should be considered.